IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAWASAN AGROPOLITAN DALAM PEMBANGUNAN EKONOMI DAERAH (Studi Pada Kecamatan Ngimbang Kabupaten Lamongan) - Wahyuni, Tri (Jurnal Administrasi Publik, 2016)
Abstract: Policy Implementation Area Development Agropolitan In Regional Economic Development (Studies in the District Lamongan Ngimbang) Lamongan Regency is a Regent with strategic position in national map because it is a part of Gerbangkartasusila and also the suburb of the central region of Surabaya Metropolitan. This position is more pronounced in the regional system when Surabaya has been acknowledged as the center of national activity. The local government of Lamongan Regency is then pushed forward to establish local government. Various policies are released by the local government to implement local economic development. One of these policies made by the local government of Lamongan Regency is agropolitan region development policy. The background of this policy is that the highest potential at Lamongan Regency remains within agriculture sector. Considering the potential in South region, especially Ngimbang District, Lamongan Regency, then the author has an interest for doing a research.   Keywords: Policy implementation, Public policy, Agropolitan   Abstrak: Implementasi Kebijakan Pengembangan Kawasan Agropolitan Dalam Pembangunan Ekonomi Daerah (Studi Pada Kecamatan Ngimbang Kabupaten Lamongan) Kabupaten Lamongan sebagai salah satu Kabupaten yang terletak pada posisi strategis skala Nasional yaitu termasuk dalam Gerbangkartasusila plus dengan pusat di Metropolitan Surabaya dan secara sistem perwilayahan dengan ditetapkannya Surabaya sebagai pusat kegiatan Nasional. Hal tersebut mendorong Pemerintah Daerah Kabupaten Lamongan untuk terus melaksanakan pembangunan wilayah. Berbagai macam Kebijakan dikeluarkan oleh Pemerintah Daerah dalam melaksanakan pembangunan ekonomi daerah. Salah satu kebijakan yang dikeluarkan oleh Pemerintah daerah Kabupaten Lamongan adalah kebijakan pengembangan kawasan agropolitan. Hal tersebut  dilatar belakangi oleh potensi Kabupaten Lamongan tertinggi adalah di sektor pertanian. Melihat potensi yang ada di wilayah selatan khususnya pada Kecamatan Ngimbang Kabupaten Lamongan penulis tertarik untuk menelitinya.   Kata Kunci: Impelementasi Kebijakan, Kebijakan Publik, Agropolitan